Estudo da influência da orientação solar no nível de conforto térmico de habitações de interesse social em Santa Maria - RS - Lima, Kananda Fernandes de Sousa (2021)
The study of the thermal comfort level in buildings has become a useful tool to measure the user's relationship with the designed environment. Based on an adequate project implementation, considering construction characteristics and the orientation of openings and envelopes, it is possible to offer several possibilities of thermal conditions in a single space. In order to provide better comfort levels to buildings, the application of solutions based on bioclimatic zoning can improve adaptability to local thermal conditions. In view of the aspects raised, this study presents a research on the level of thermal comfort in single-family social housing in the city of Santa Maria, Rio Grande do Sul, analyzing the influence of solar orientation. To conduct the research, multi-method steps were established based on the application of qualitative questionnaires during winter and summer and computer simulations through the EnergyPlus software, having as analysis of the results the adaptive model with acceptability of 80% (ASHRAE 55). In the case study, housing units implemented by the Minha Casa Minha Vida program were chosen in the Dom Ivo, Leonel Brizola and Zilda Arns residential complexes. In the three sets, two building typologies are verified, and these are the basis for the object of analysis. Through the interview method, it was observed in the results that the current season influenced the users' answer profile, showing more discomfort due to cold in the winter survey data and a higher sensation of heat during the interviews carried out in the summer. During the computer simulation method, significant levels of thermal discomfort were perceived in the dwellings, especially for cold. The solar orientation units with the highest comfort ratio were facing northwest and southwest. However, in the process of finalizing the research, a model was simulated, based on the solar orientation building with one of the worst results, proposing construction solutions capable of mitigating levels of thermal discomfort.